PENGARUH KARAKTERISTIK DEWAN KOMISARIS, KARAKTERISTIK PERUSAHAAN, DAN REPUTASI AUDITOR TERHADAP PENGUNGKAPAN MANAJEMEN RISIKO: (Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Tahun 2017 – 2020) - Ayudya Rahmawati; Andry Sugeng (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to prove empirically the effect of the characteristics of the board of commissioners, firm size, leverage, public ownership, and auditor reputation on risk management disclosure. This research was conducted in property and real estate companies. The research method used is quantitative associative. The type of data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (IDX) in 2017–2020. Samples were collected using purposive sampling method. The number of companies that were used as research samples were 44 companies with a research period of 4 (four) years, so that 176 observational data were obtained. Processing data using Microsoft Office Excel Program and Statistics Program Eviews 9 by collecting related data and then analyzing descriptive statistics, regression model analysis, regression model selection, classical assumption test, coefficient of determination (R2), panel data regression analysis, statistical test F and statistical test t. The results of the F statistical test of the characteristics of the board of commissioners, firm size, leverage, public ownership, and auditor reputation have an effect on risk management disclosure. The results of the t-statistical test of the characteristics of the board of commissioners, firm size, leverage, and public ownership partially have a positive effect on risk management disclosure, while the auditor's reputation partially has no effect on risk management disclosure.